Reformasi Birokrasi Dalam Meningkatkan Kualitas Pelayanan Publik (Studi Pada Badan Pelayanan Perizinan Terpadu (BPPT) Kabupaten Sidoarjo) - Rachmawati, Riska (Jurnal Administrasi Publik, 2016)
Abstract: Reformation Of Bureaucracy In Enhancing The Quality Of Public Services. The study of public administration said that one of the government’s jobs is giving the best service to the society. But, in fact, there are many obstacles that arestill found in some of the public services. Therefore, the reformation of public administration in government’s bureaucracy is urgently needed in order to create the best public service quality. The result of the research shows that BPPT Sidoarjo was able to conduct bureaucracy reformation to improve the quality of public services. The transformation of institution’s form and the number of the authority has been renewed since 2001 until 2014. BPPT of Sidoarjo District has arranged the management, those are: Conducted SPP (Public Service Standard) and SOP (Standard Operating Procedure) which has been determined. Optimized and developed the technology. Got a very good predicate from the survey of public satisfaction Be able to respond all of the public complaints. The human resources of the institution have also been improved by doing several trainings in order to work more professionally. Besides that, there are several factors that affect the success of the implementation of bureaucracy reformation, those are: The commitment of the head toward the employees. The disposition of the employees based on their skills. The facilities of maintenance that are adequate. There are also some obstacles, those are: The lack of permission service socialization. The lack of coordination among the relevant technical SKPD. Therefore, the deep socialization to all of the society and the discipline of the work among the relevant SKPD are needed in order to give the maximum service to the public. Key words: bureaucracy reformation and public service quality.   Abstrak: Reformasi Birokrasi Dalam Meningkatkan Kualitas Pelayanan Publik. Studi administrasi publik menyatakan bahwa salah satu tugas pemerintah adalah memberikan pelayanan yang baik kepada masyarakat. Namun, pada kenyataanya, beberapa pelayanan publik khususnya pada pelayanan perizinan masih ditemukan banyak kendala. Maka dari itu, reformasi pelayanan publik pada birokrasi pemerintah sangat dibutuhkan untuk menciptakan kualitas pelayanan publik yang baik. Hasil penelitian menunjukkan bahwa BPPT Sidoarjo telah dapat melaksanakan reformasi birokrasi untuk meningkatkan kualitas pelayanan publik perubahan bentuk lembaga dan jumlah kewenangan telah diperbaharui dari tahun 2001 sampai 2014. BPPT Kabupaten Sidoarjo telah menata ketatalaksanaan antara lain yaitu: melaksanakan SPP (Standar Pelayanan Publik) dan SOP (Standar Operasional Prosedur) yang telah ditetapkan. Mengoptimalkan dan mengembangkan tekonologi yang ada. Mendapat predikat sangat baik dari survei kepuasan masyarakat. Dapat merespon semua pengaduan masyarakat yang ada. Sumber daya manusianya juga dibentuk untuk bekerja lebih professional melalui serangkaian diklat. Meskipun begitu terdapat beberapa faktor yang mempengaruhi keberhasilan pelaksanaan reformasi birokrasi yaitu: Komitmen atasan terhadap pegawai. Penempatan pegawai sesuai skill. Sarana prasarana yang memadai. Terdapat juga faktor yang menghambat yaitu: Kurangnya sosialisasi pelayanan perizinan. Kurangnya koordinasi antar SKPD teknis terkait. Maka dari itu dibutuhkan sosialisasi mendalam kepada seluruh masyarakat dan kedisiplinan kerja antar SKPD terkait agar pelayanan dapat dilakukan lebih maksimal. Kata Kunci: reformasi birokrasi dan kualitas pelayanan publik.